2020
DOI: 10.1111/mcn.12972
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and diet quality during pregnancy and low birthweight: The PRINCESA cohort

Abstract: Although the isolated effects of several specific nutrients have been examined, little is known about the relationship between overall maternal diet during pregnancy and fetal development and growth. This study evaluates the association between maternal diet and low birthweight (LBW) in 660 pregnant women from the Pregnancy Research on Inflammation, Nutrition,& City Environment: Systematic Analyses (PRINCESA) cohort in Mexico City. Using prior day dietary intake reported at multiple prenatal visits, diet was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Meanwhile, the limitation is that because this is a cross-sectional study, the authors cannot confirm a temporal relationship between exposure and outcome variables. Another limitation is that it did not investigate some of the known risk factors from previous studies for LBW, including dietary and nutritional factors 42,43 , genetic factors, and [44][45][46] , as well as pollution and environmental factors 47,48 . This limitation is more due to limited secondary data from the 2017 IDHS.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Meanwhile, the limitation is that because this is a cross-sectional study, the authors cannot confirm a temporal relationship between exposure and outcome variables. Another limitation is that it did not investigate some of the known risk factors from previous studies for LBW, including dietary and nutritional factors 42,43 , genetic factors, and [44][45][46] , as well as pollution and environmental factors 47,48 . This limitation is more due to limited secondary data from the 2017 IDHS.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A posteriori dietary patterns, therefore, provide insight into dietary behaviors as they reflect on actual food or nutrient intake [ 21 ]. Although these two methods are regarded to provide complementary information with regard to the overall diet [ 21 ], only a few studies [ 22 , 23 , 24 ] have used both methods to explore the maternal diet during pregnancy. Furthermore, to our knowledge, all studies reporting on a posteriori dietary patterns during pregnancy used foods or food groups as variables to determine patterns.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the findings from the Growing Up in Singapore Towards Healthy Outcomes Study [ 79 ] and the Infant Feeding Practices Study II [ 80 ]. However, few other studies have shown that higher adherence to a good quality diet during pregnancy is associated with lower risk of having a low birthweight baby [ 81 , 82 , 83 ]. These inconsistent results between studies can be attributed to the use of different diet-quality scores.…”
Section: Discussionmentioning
confidence: 99%